2016
DOI: 10.1002/2327-6924.12377
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and outcomes of a nurse practitioner–run chest pain evaluation unit

Abstract: Background Every year, more than 5 million patients seek medical care for chest pain. Objective The goal of this study was to evaluate test utilization and outcomes of a nurse practitioner (NP)‐based chest pain unit and compare results to data previously reported from our institution. Design, setting, and participants The records from 814 consecutive patients with chest pain admitted to the NP‐run unit were compared to the outcomes of 250 patients admitted to a separate hospitalist‐run unit at a New York City … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A similar evaluation has been forthcoming from Masso and Thompson (2017), who criticizes the lack of context in NP research to date, resulting in difficulties related to the transferability of the evidence. The literature related to NPs effect on health care, such as patient outcomes, is limited to a single‐role, single‐centre research over a limited time frame (Tucker & Bernard, 2015; Wand, White, Patching, Dixon, & Green, 2012; Zhu, Islam, & Bergmann, 2016). Litchman et al (2018), supported this as they have identified gaps in NP research related to patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A similar evaluation has been forthcoming from Masso and Thompson (2017), who criticizes the lack of context in NP research to date, resulting in difficulties related to the transferability of the evidence. The literature related to NPs effect on health care, such as patient outcomes, is limited to a single‐role, single‐centre research over a limited time frame (Tucker & Bernard, 2015; Wand, White, Patching, Dixon, & Green, 2012; Zhu, Islam, & Bergmann, 2016). Litchman et al (2018), supported this as they have identified gaps in NP research related to patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, their impact is contingent upon receiving education, preparing them for rural healthcare's unique challenges. Traditional nursing programs often fall short in this regard, highlighting the need for specialized curriculum development tailored to rural healthcare's intricacies [8,9]. This study aims to evaluate the demand for APNs in rural community hospitals, targeting the specific needs of rural healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it empowers patients and makes them feel respected and more compliant with treatment plans, in turn improving their prognosis [10]. Many studies highlighted that NPs provide medical care equivalent to that of physicians and facilitate access to healthcare [11][12][13]. Igrarshi et al [4], interviewed NPs in Japan and discovered that NPs can improve the quality of healthcare by proposing practical solutions to problems faced by patients and medical organizations.…”
Section: Introductionmentioning
confidence: 99%